2015
DOI: 10.1088/0004-637x/814/1/61
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Co Observation of the Carbon Star Cit 6 Revealing the Spiral Structure and a Nascent Bipolar Outflow

Abstract: CIT 6 is a carbon star in the transitional phase from the asymptotic giant branch (AGB) to the protoplanetary nebulae (pPN). Observational evidences of two point sources in the optical, circumstellar arc segments in an HC 3 N line emission, and a bipolar nebula in near-infrared provide strong support for the presence of a binary companion. Hence, CIT 6 is very attractive for studying the role of companions in the AGB-pPN transition. We have carried out high resolution 12 CO J=2-1 and 13 CO J=2-1 observations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
(83 reference statements)
4
29
0
Order By: Relevance
“…We note that indications of spiral-shell patterns have been observed in the circumstellar molecular line images of AGB stars with high sensitivity and resolution [3,10,11,[25][26][27][28]. Observations such as these enable detailed investigations of the entire nebular structure on spatial scales ranging from several to several thousand times the typical size of an AGB star and facilitate understandings of the morphological patterns of the AGB, pPN, and PN phases.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…We note that indications of spiral-shell patterns have been observed in the circumstellar molecular line images of AGB stars with high sensitivity and resolution [3,10,11,[25][26][27][28]. Observations such as these enable detailed investigations of the entire nebular structure on spatial scales ranging from several to several thousand times the typical size of an AGB star and facilitate understandings of the morphological patterns of the AGB, pPN, and PN phases.…”
mentioning
confidence: 75%
“…Many of these nebulae consist of outer structures that are nearly spherical (spiral/shell/arc/halo) and inner structures that are highly asymmetric (bipolar/multipolar) [1,2]. The coexistence of such geometrically distinct structures is enigmatic because it hints at the simultaneous presence of both wide and close binary interactions, a phenomenon that has been attributed to stellar binary systems with eccentric orbits [3]. Here we report new high-resolution molecular-line observations of the circumstellar spiral-shell pattern of AFGL 3068, an asymptotic giant branch (AGB) star transitioning to the pPN phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The low mass secondary in orbit around AGB star can shape the AGB wind into a bipolar outflow structure (Nordhaus & Blackman 2006). An observational example is L2 Puppis Kervella et al 2016). Chen et al (2016b) found that 3D hydrodynamic simulation of L2 Puppis and found very good agreement with the morphology and spectral energy distribution.…”
Section: Bipolar Outflowmentioning
confidence: 92%
“…The number of examples is steadily increasing, e.g., CW Leo Decin et al 2015), RW LMi (Dinh-V-Trung 2009;Claussen et al 2011;Kim et al 2015), R Scl , R Aqr and W Aql (Mayer et al 2013), and π 1 Gru . A prominent example is that of the dust and gas spiral towards AFGL3068 (Mauron and Huggins 2006;Kim et al 2017), Fig.…”
Section: Impacts Of Companions On Cse Morphologymentioning
confidence: 99%